A seed is the start - Stewart, Melissa (National Geographic kids., 2018)
Beautiful photography and lyrical text pair with comprehensive picture captions in award-winning author Melissa Stewart's story about the surprisingly diverse world of seeds. Learn all about the plant cycle, from how seeds grow, the fascinating ways they travel, and what it takes for a seed to become a plant.